Patterns of Gastrointestinal Symptoms of Covid-19 Patients in a University Hospital of Bangladesh - Islam, Samprity; Islam, Sumona; Tabassum, Nourin; Islam, Nafizul; Tarik, Imtiaz; Alam, Md Razibul (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
The World has experienced a devastating pandemic of COVID-19 caused by SARS-CoV-2 that started at March, 2020 and ended in May, 2023. Most patients of COVID-19, presented with respiratory symptoms and signs. But the number of COVID-19 patients experiencing gastrointestinal symptoms were also significant. The spectrum of gastrointestinal symptoms in the second wave of COVID-19 was observed in this study from July 2020 to September 2020 with an aim to describe the frequency of occurrence and the possible timing of onset and duration of these symptoms. This cross-sectional study was carried out in the COVID-19 outpatient (triage of fever clinic) and COVID dedicated inpatient department of Bangabandhu Sheikh Mujib Medical University (BSMMU) involving at least 79 consecutive patients who were RT-PCR positive for coronavirus 2 (SARS-CoV-2). Gastrointestinal symptoms including anorexia, nausea, vomiting, altered taste, diarrhoea, haematemesis or melena were recorded precisely by face to face interview maintaining proper infection control protocol. Among the 79 COVID-19 patients, 70.88% patients had at least one gastrointestinal symptom & the rest had no GI symptom. Most patients suffered from anorexia (70.88%), followed by diarrhoea (62.02%), nausea (41.77%), loss of taste (36.70%), vomiting (32.90%) & abdominal pain (7.59%), melena (2.53%). Diarrhoea was mild in most cases. The mean duration of diarrhoea and dysgeusia/loss of taste was 2.83 days and 5.8 days respectively. Mean duration of exposure to COVID 19 patient and onset of diarrhoea and dysgeusia was 7.69 days and 3.8 days respectively. This study did not exhibit any association between GI symptoms and severity of the disease. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):07-11